Answer to Q1:
f⁻¹(x) = 3-x / 6 = g(x)
Explanation:
We have given two function.
f(x) = -6x+3 and g(x) = (3-x) / 6
We have to show that given two functions are inverse of each other.
Let f(x) = y
y = -6x+3
We have to separate x from above function.
Adding -3 to both sides of above equation, we have
y-3 = -6x+3-3
y-3 = -6x
Dividing by -6 to both sides of above equation , we have
(y-3) / (-6) = -6x / -6
3-y / 6 = x
Swapping above equation, we have
x = 3-y / 6
Putting x = f⁺¹(y) in above equation, we have
f⁺¹(y) = 3-y / 6
Replacing y with x, we have
f⁻¹(x) = 3-x / 6 = g(x)
Hence, f and g are inverse functions.
Answer to Q2:
f⁻¹(x) = √5-x/3 = g(x)
Explanation:
We have given two functions.
f(x) = -3x²+5
g(x) = √5-x/3
Let y = f(x)
y = -3x²+5
We have to separate x from above equation .
Adding -5 to both sides of above equation, we have
y-5 = -3x²+5-5
y-5 = -3x²
Dividing by-3 to both sides of above equation , we have
(y-5) / (-3) = -3x²/(-3)
5-y / 3 = x²
Swapping above equation, we have
x² = 5-y/3
Taking square root to both sides of above equation, we have
x = √5-y / 3
Putting x = f⁻¹(y) in above equation , we have
f⁻¹(y) = √5-y / 3
replacing y with x , we have
f⁻¹(x) = √5-x / 3 = g(x)
Hence , f and g are inverse functions.